KORELASI ANTARA KECERDASAN SPIRITUAL DENGAN SIKAP DISIPLIN SISWA DI MADRASAH ALIYAH NEGERI (MAN) KOTA BATU - Nabila Maya Dalillah; Rosichin Mansur; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the correlation between spiritual intelegence and discipline attitude os students in Madrasah Aliyah Negeri (MAN) Kota Batu. The problem in this study is how the spiritual intelegence of students in the MAN Kota Batu , how students are disciplined in the MAN Kota Batu and is there a correlation between spiritual intelegence and student discipline in the MAN Kota Batu. The method in this study in quantitative. Data collection techniques use observation, interviews, documentation, and questionnaires. As for the questionnaire result calculation using the frequency distribution formula, while in knowing the correlation using the prodect moment formula. The results of the study showed that there was a significant correlation between spiritual intelegence and the discipline of students with a contribution of 0,15%. The relationship between the two is very low or weak so it is often ignored or not use.